Effects of Transcranial Direct Current Stimulation on Motor Function in Children 8–12 Years With Developmental Coordination Disorder: A Randomized Controlled Trial - Grohs, Melody N.; Craig, Brandon T.; Kirton, Adam; Dewey, Deborah (Frontiers in Human Neuroscience, 2020)
Background and Objectives: Developmental coordination disorder (DCD) is a neurodevelopmental motor disorder occurring in 5-6% of school-aged children. It is suggested that children with DCD show deficits in motor learning. Transcranial direct current stimulation (tDCS) enhances motor learning in adults and children but is unstudied in DCD. We aimed to investigate if tDCS, paired with motor skill training, facilitates motor learning in a pediatric sample with DCD. Methods: Twenty-eight children with diagnosed DCD (22 males, mean age: 10.62 ±1.44 years) were randomized and placed into a treatment or sham group. Anodal tDCS was applied (1mA, 20min) in conjunction with fine manual training over 5 consecutive days. Children’s motor functioning was assessed with the Purdue Pegboard Test and Jebsen-Taylor Hand Function Test at baseline, post-intervention and 6 weeks following intervention. Group differences in rates of motor learning and skill transfer/retention were examined using linear mixed modelling and repeated measures ANOVAs, respectively. Results: There were no serious adverse events or drop-outs and procedures were well tolerated. Independent of group, all participants demonstrated improved motor scores over the 5 training days (F:69.280, p<0.001, 95% CI [0.152, 0.376]), with no skill decay observed at retention. There was no interaction between intervention group and day (F:2.998, p=0.086, 95% CI [-0.020, 0.297]). Conclusion: Children with DCD demonstrate motor learning with long-term retention of acquired skill. Motor cortex tDCS did not enhance motor learning as seen in other populations. Before conclusions of tDCS efficacy can be drawn, additional carefully designed trials with reproducible results are required.